Gravity Wave Breaking and Vortex Ring Formation Observed by PMC Turbo - Geach, Christopher; Hanany, Shaul; Fritts, D. C.; Kaifler, Bernd; Kaifler, Natalie; Kjellstrand, Bjorn; Williams, Bifford P.; Eckermann, Stephen D.; Miller, Amber; Jones, Glenn; Reimuller, Jason (Journal of Geophysical Research: Atmospheres, 2020)
Polar mesospheric cloud (PMC) imaging and lidar profiling performed aboard the 5.9 day PMC Turbo balloon flight from Sweden to northern Canada in July 2018 revealed a wide variety of gravity wave (GW) and instability events occurring nearly continuously at approximately 82 km. We describe one event exhibiting GW breaking and associated vortex rings driven by apparent convective instability. Using PMC Turbo imaging with spatial and temporal resolution of 20 m and 2 s, respectively, we quantify the GW horizontal wavelength, propagation direction, and apparent phase speed. We identify vortex rings with diameters of 2‐5 km and horizontal spacing comparable to their size. Lidar data show GW vertical displacements of ±0.3 km. From the data, we find a GW intrinsic frequency and vertical wavelength of 0.009 ± 0.003 rad s‐1 and 9 ± 4 km, respectively. We show that these values are consistent with the predictions of numerical simulations of idealized GW breaking. We estimate the momentum deposition rate per unit mass during this event to be 0.04 ± 0.02 m s‐2 and show that this value is consistent with the observed GW. Comparison to simulation gives a mean energy dissipation rate for this event of 0.05‐0.4 W kg‐1, which is consistent with other reported in‐situ measurements at the Arctic summer mesopause.